Effect of laser surface melting on intergranular corrosion behaviour of aged austenitic and duplex stainless steels - Kwok, C.T.; Lo, K.H.; Chan, W.K.; Cheng, F.T.; Man, H.C. (Corrosion science, 2011)
► Chromium carbides in aged ASSs were completely removed after LSM. ► Sigma and secondary austenite in aged DSSs were eliminated after LSM. ► After LSM, IGC resistance of aged ASSs and DSSs was improved as reflected by the reduction in DOS. ► IGC attack occurs at the Cr-depleted grain or phase boundaries for the aged specimens. ► IGC attack occurs at interdentritic boundaries of austenite-ferrite for aged specimens after LSM. In the present study, the effect of laser surface melting (LSM) on intergranular corrosion behaviour of aged austenitic stainless steels (UNS S30400, S31603, S32100 and S34700) and aged duplex stainless steels (UNS S31803 and S32950) were investigated. LSM of the aged stainless steels was carried out using a 2.5 kW CW Nd:YAG laser. The microstructure of the aged stainless steels after LSM depends on their compositions. After LSM, the aged austenitic stainless steels mainly contain austenite (γ) with some ferrite (δ) as the minor phase, but the carbide phases are completely eliminated. For the aged duplex stainless steels after LSM, δ becomes the major phase and the δ/γ phase balance is disturbed, whereas the sigma (σ) phase is eliminated. The degree of sensitization ( DOS) and corrosion morphology of the aged stainless steels before and after LSM were determined by the double loop electrochemical potentiokinetic reactivation (DL-EPR) using a potentiostat and SEM observation, respectively. Desensitization of the aged stainless steels has been successfully achieved by LSM and their intergranular corrosion resistance is found to be significantly enhanced as reflected by the decrease in DOS due to dissolution of the carbides or σ phase, which reduced Cr depletion or the possibility of solute segregation at the grain or phase boundaries, despite the presence of δ and disturbance of δ/γ phase balance.